Factors Affecting Mastitis Cases and the Correlations of Somatic Cell Count with Milk Production in Holstein Cows - Savaş Atasever; Violetta Tóth; Edit Mikóné Jónás (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study was to determine the factors affecting mastitis cases and to estimate the correlations of somatic cell count (SCC) with milk yield in Holstein cows. The study was conducted in two private dairy farms in Hódmezõvásárhely, South-Hungary. A total of 882 Holstein cows were tested by SCC, fat and protein contents of milk monthly intervals. To test milk SCC and components, two groups were designed, and to examine effect of parity on first mastitis day (FMD) and total mastitis cases (TMC), four groups were divided. It was noted that higher SCC caused to higher TMC. While cows had higher protein content exposed to higher FMD and TMC, cows had lower daily milk yield (DMY) had higher values by mastitis case parameters. In parity evaluation, only primiparous cows had statistically lower TMC. The cows with lower SCC were found in advance in change of milk yield (CMY) up to 6.858±0.947 kg. A negative correlation coefficient was estimated between SCC and DMY. Finally, monitoring SCC of milk is offered to prevent milk production losses and new mastitis occurrences in the herds.